If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = x + 1 + -6x Reorder the terms: 1 = 1 + x + -6x Combine like terms: x + -6x = -5x 1 = 1 + -5x Add '-1' to each side of the equation. 1 + -1 = 1 + -1 + -5x Combine like terms: 1 + -1 = 0 0 = 1 + -1 + -5x Combine like terms: 1 + -1 = 0 0 = 0 + -5x 0 = -5x Solving 0 = -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 0 + 5x = -5x + 5x Remove the zero: 5x = -5x + 5x Combine like terms: -5x + 5x = 0 5x = 0 Divide each side by '5'. x = 0 Simplifying x = 0
| 0.15-1.25=0 | | 9g-6g-1=14 | | X+6=9+x | | 2=3x^2-4x | | 3x+112=7x+40 | | 14=2(j-6) | | 10-5q=-4-7q | | 2.36/4 | | 3x-2/3-x-1/3=1 | | g(r)=-5r | | 10t-5t+2=7 | | 5(x-4)+2x+15=44 | | 2(x-2)=2/3(4x=2)=2 | | a+4=6+2a | | 6(y+4)=2(y+8) | | 6p-3-p=2 | | 7h-0i=99-98k | | 10p-3p-20=1 | | 0.15t-2.50=0 | | 7h-0i= | | 7a-5=-4a-27 | | -10x-37=-3x+61 | | j-j+5j-4j=15 | | 5-5r=9-3r | | 9m-15=28 | | 4(h-2)=2h+8 | | 7(2x+5)+3(x-8)=3(2x+33) | | 2x+1.5x=15 | | 7x+8=8(x-3) | | whatisx-10x-3-2.5x+20=67 | | 4-0.5x=1/6x | | 1+5n+6=7+5n |